2016
DOI: 10.1121/1.4943554
|View full text |Cite
|
Sign up to set email alerts
|

Auditory evoked potentials in the auditory system of a beluga whale Delphinapterus leucas to prolonged sound stimuli

Abstract: The effects of prolonged (up to 1500 s) sound stimuli (tone pip trains) on evoked potentials (the rate following response, RFR) were investigated in a beluga whale. The stimuli (rhythmic tone pips) were of frequencies of 45, 64, and 90 kHz at levels from 20 to 60 dB above threshold. Two experimental protocols were used: short- and long-duration. For the short-duration protocol, the stimuli were 500-ms-long pip trains that repeated at a rate of 0.4 trains/s. For the long-duration protocol, the stimuli were cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…1 μPa) than the thresholds of 45 to 50 dB found in our previous investigations in belugas at the same frequency and with the use of the same threshold-determination technique (Popov et al, 2013(Popov et al, , 2016. Most probably, the increased baseline threshold in the present study is a result of the method of the test stimulus presentation: during each trial, stimuli of randomly varied levels were presented in an interleaving manner (see Materials and methods, Test stimuli).…”
Section: Discussion Restriction For the Investigated Level Rangementioning
confidence: 37%
See 1 more Smart Citation
“…1 μPa) than the thresholds of 45 to 50 dB found in our previous investigations in belugas at the same frequency and with the use of the same threshold-determination technique (Popov et al, 2013(Popov et al, , 2016. Most probably, the increased baseline threshold in the present study is a result of the method of the test stimulus presentation: during each trial, stimuli of randomly varied levels were presented in an interleaving manner (see Materials and methods, Test stimuli).…”
Section: Discussion Restriction For the Investigated Level Rangementioning
confidence: 37%
“…Most probably, the increased baseline threshold in the present study is a result of the method of the test stimulus presentation: during each trial, stimuli of randomly varied levels were presented in an interleaving manner (see Materials and methods, Test stimuli). This stimuli presentation could result in hearing adaptation to supra-threshold sound levels (Popov et al, 2016) manifesting in the increased threshold estimate that characterized the hearing sensitivity not in silence but in a certain sound background. Despite this disadvantage, we used the interleaving manner of stimulus presentation because, otherwise, post-exposure recovery of responses to different stimulus level could not be traced equally.…”
Section: Discussion Restriction For the Investigated Level Rangementioning
confidence: 99%
“…To quantitatively characterize the temporal dynamics of the RFR after the stimulus increase/decrease, the dependence of the RFR amplitude on stimulation time was approximated by an exponential function within a time range from 10 to 1000 ms. We have previously shown in the beluga that an RFR decay during prolonged stimulation may be approximated by two exponents with time constants of 30 to 80 ms and 3.1 to 17.6 s [ 16 ]. The time constant of several seconds is beyond the duration of the 1000 ms analysis window in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous investigation [ 16 ] showed that in the beluga, the time course of the response amplitude during prolonged stimulation can be satisfactorily approximated by a combination of two exponents: a “short” exponent with a time constant from 30 to 80 ms and a “long” exponent with a time constant from 3.1 to 17.6 s. These two exponents may reflect two adaptation processes known as the short-term and long-term adaptation. In the present study, we ignored the “long” adaptation because response variations were investigated within a time window of no longer than 1000 ms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation